2013
DOI: 10.1002/ejoc.201300167
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Scope of the Aza‐Fischer Synthesis of 4‐ and 6‐Azaindoles

Abstract: Fischer indole cyclization has recently been described as an efficient approach to the synthesis of azaindoles bearing electron‐donating groups. We now show that this cascade reaction can be very efficient for the formation of a wider range of 4‐ and 6‐azaindoles by using microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…SL651498 2 , a GABA A receptor agonist, reached phase IIb clinical trials for the treatment of generalized anxiety disorder and muscle spasms . The semisaturated pyrrolo-pyridones in contrast have been far less explored mainly due to their poor synthetic tractability; however, Haydar et al demonstrated that compounds containing such skeletons, such as 3 , had biological activity against HIV . Evidently, both semi-aromatic and fully aromatic fused tricyclic pyrrolo-pyridinones like 4 , bearing functional groups as depicted in Figure , are attractive building blocks for medicinal chemistry and would be more widely used if a facile synthetic approach to them was developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SL651498 2 , a GABA A receptor agonist, reached phase IIb clinical trials for the treatment of generalized anxiety disorder and muscle spasms . The semisaturated pyrrolo-pyridones in contrast have been far less explored mainly due to their poor synthetic tractability; however, Haydar et al demonstrated that compounds containing such skeletons, such as 3 , had biological activity against HIV . Evidently, both semi-aromatic and fully aromatic fused tricyclic pyrrolo-pyridinones like 4 , bearing functional groups as depicted in Figure , are attractive building blocks for medicinal chemistry and would be more widely used if a facile synthetic approach to them was developed.…”
mentioning
confidence: 99%
“…We subsequently needed access to saturated analogues of pyrido­[3,4- b ]­indol-1-ones 12a such as compound 15 . Literature precedent for these ring systems remains very limited and is only achieved by long linear synthetic sequences. , We were encouraged to discover the work of Suzenet and Moody who both utilized a Fischer indolisation strategy to synthesize compounds like 14 (Scheme ). Both approaches required an electron-donating group ortho or para on the aryl group linked to the hydrazine to effect efficient indole ring formation.…”
mentioning
confidence: 99%
“…Other existent methods emanating from Hegedus-Mori-Heck, 9 Fischer, 10 or Madelung 11 approaches use palladium and strongly basic or acidic conditions with high temperatures. Many syntheses do not provide access to substitution of the C2-aryl moiety or the full scope of azaindole regioisomers.…”
mentioning
confidence: 99%